Rethinking the Andes-Amazonia Divide : A cross-disciplinary exploration (Book collections on Project MUSE., 2020)
Rethinking the Andes-Amazonia Divide brings together archaeologists, linguists, geneticists, anthropologists, ethnohistorians and historians to explore the meeting of the Andes and Amazonia, from deepest prehistory up to the European colonial period.